PENERAPAN SURAT DAKWAAN SUBSIDAIR DALAM KEMATIAN ANAK: Application Of Subsidiary Indictment In Child Death Cases - Antonius Sihmiyanto; Maria Silvya E. Wangga (AMICUS CURIAE, 2025)
The indictment is a crucial part of the criminal justice process, because it plays a role in directing the course of the case examination in court. In cases involving children as defendants, the preparation of the indictment must be prepared by considering the principles of child protection as stated in Law No. 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA). This study focuses on a juvenile criminal case involving a juvenile defendant who was charged with committing abuse resulting in death. The indictment prepared by the prosecutor includes Article 340, Article 338, and Article 351 Paragraph (3) of the Criminal Code with an alternative indictment. The identification problem studied in this study is the Application of Subsidiary Indictments in Cases of Child Death Based on the Criminal Procedure concerning the Juvenile Justice System. The research method used is the normative legal method with a descriptive-analytical approach. The research data was obtained through a literature study of primary, secondary, and tertiary legal materials analyzed qualitatively. The results of the study indicate that although the application of subsidiary charges provides flexibility in the evidentiary process, in the context of juvenile justice, an approach that emphasizes restorative justice is needed.